2013
DOI: 10.1007/s12663-013-0512-9
|View full text |Cite
|
Sign up to set email alerts
|

Peripheral Neurectomy: Minimally Invasive Surgical Modality for Trigeminal Neuralgia in Indian Population: A Retrospective Analysis of 20 Cases

Abstract: Peripheral neurectomy is one of the minimally invasive and expeditious forms of surgical modality for the treatment of trigeminal neuralgia. This treatment option is cost effective and provides long term relief from neuralgic pain.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
7
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 14 publications
2
7
0
Order By: Relevance
“… 8 Most of the studies done for peripheral neurectomy were published 20–50 years ago, demonstrating an average pain relief period of 24–33 months after surgery, with follow-up periods up to 9 years. 9 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 8 Most of the studies done for peripheral neurectomy were published 20–50 years ago, demonstrating an average pain relief period of 24–33 months after surgery, with follow-up periods up to 9 years. 9 …”
Section: Discussionmentioning
confidence: 99%
“…The immediate outcomes of peripheral neurectomies are usually excellent, but long-term efficacy in classic TN is variable. 10 Regarding the follow-up after peripheral neurectomy, Chandan et al 9 suggest postoperative day 2, 7, 30, and then every 6 months for up to 3 years.…”
Section: Discussionmentioning
confidence: 99%
“…24 There have been some revivals in the last 5 years as more oral surgeons in the Indian subcontinent reported their use for treating patients who were living in the rural area and were deprived socio-economically of modern neurosurgical facilities. 7,25,40,41 Proponents of peripheral neurectomy think that this procedure still has a role to play with the elderly, medically compromised patients or those not keen to be subjected to extensive neurosurgery. 18,24,39 The surgical techniques employed in this case were essentially the same as described by Hong-Sai.…”
Section: Discussionmentioning
confidence: 99%
“…10 The average pain free period achieved has been reported to be longer than that accorded by cryotherapy and lasted between 24-36 months similar to that reported by many authors. 12,25,30 Grantham and Segerberg 30 who electrocauterized the remaining nerve stump after performing nerve avulsion, reported to have achieved a wide range, from no improvement to pain relief up to 8 years. Yadav et al 7 however, recently reported that 25% of their Indian patients who underwent peripheral neurectomy suffered from recurrence of neuralgia within 6 months post surgery.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation